Perspectives on biomedical HIV prevention options among women who inject drugs in Kenya. Issue 3 (4th March 2018) - Bazzi, Angela Robertson; Yotebieng, Kelly A.; Agot, Kawango; Rota, Grace; Syvertsen, Jennifer L.
ABSTRACT: Due to heightened vulnerability to HIV from frequent engagement in sex work and overlapping drug-using and sexual networks, women who inject drugs should be a high priority population for pre-exposure prophylaxis (PrEP) and other biomedical HIV prevention tools. Kenya is one of the first African countries to approve oral PrEP for HIV prevention among "key populations, " including people who inject drugs and sex workers. The objective of this study was to explore preferences and perceived challenges to PrEP adoption among women who inject drugs in Kisumu, Kenya. We conducted qualitative interviews with nine HIV-uninfected women who inject drugs to assess their perceptions of biomedical HIV interventions, including oral PrEP, microbicide gels, and intravaginal rings. Despite their high risk and multiple biomedical studies in the region, only two women had ever heard of any of these methods. All women were interested in trying at least one biomedical prevention method, primarily to protect themselves from partners who were believed to have multiple other sexual partners. Although women shared concerns about side effects and product efficacy, they did not perceive drug use as a significant deterrent to adopting or adhering to biomedical prevention methods. Beginning immediately and continuing throughout Kenya's planned PrEP rollout, efforts are urgently needed to include the perspectives of high risk women who use drugs in biomedical HIV prevention research and programing.